Cardiac Autonomic Control in High Level Brazilian Power and Endurance Track-and-Field Athletes - Abad, C. C. C.; do Nascimento, A. M.; Gil, S.; Kobal, R.; Loturco, I.; Nakamura, F. Y.; Mostarda, C. T.; Irigoyen, M. C. (International Journal of Sports Medicine, 2014)
The autonomic nervous system (ANS) has an important role in physical performance. However, the cardiac ANS activity in high-level track and field athletes has been poorly explored. Thus, we tested the hypothesis that endurance and power athletes would present a markedly different cardiac autonomic control at rest. We analyzed the cardiac ANS by means of time and frequency domains heart rate variability (HRV) analyses and by symbolic analysis. Endurance athletes showed higher pulse interval than power athletes (1 265±126 vs. 1 031±98 ms respectively; p<0.05). No differences were found in time and frequency domains between the groups. However, the LF%, HF% and LF/HF ratio presented high effect sizes (1.46, 1.46 and 1.30, respectively). The symbolic analysis revealed that endurance athletes had higher 2V parasympathetic modulation (36±6.5) than power athletes (24±9.3; p<0.05). A reduced 0V sympathetic modulation was observed in endurance athletes (21±9.9) compared to power athletes (33±11; p<0.05 and ES=1.30). Our results suggest greater parasympathetic modulation and less sympathetic modulation in endurance athletes compared to power athletes. Additionally, the type of HRV analysis needs to be chosen with well-defined criteria and caution because their use in assessing cardiac autonomic modulation can interfere with the interpretation of results. In practical terms, symbolic analysis appears to better discriminate between cardiac autonomic activities of athletes with different training backgrounds than frequency domain analysis.
Keywords: autonomic nervous system; heart rate; athletes; sports; exercise; athletic performance